Archive of crete [Girit Arşivi] - (:unkn) unknown (University and Research Librarians Association (UNAK), 2014)
Even the name of Isle of Crete can bring to mind lots of images: For example some historical sites to visit, the noisy cities of commerce where the traffic are heavy, millions of olives trees covering the rural areas, mountains to climb However here the topic is not the inarguable natural beauties of Crete but its archive which some part of it had been lost and the other part is under the guard of several institutions. Aforesaid archive material consists of nearly 15.000 documents and more than 100.000 digital images; they are belong to the directorate of foundations in Crete and they picture the daily life of Islamic society had lived in the island. In this article, mostly given places for the documents of Crete sent to Turkey in accordance with the protocol signed in 1925 for the refugees except the Greeks who lived in Istanbul and the Turks in Western Thrace.
Keywords: Archive; Crete; Excambium; SALT